1997
DOI: 10.1074/jbc.272.8.5007
|View full text |Cite
|
Sign up to set email alerts
|

Misregulation of Stromelysin-1 Expression in Mouse Mammary Tumor Cells Accompanies Acquisition of Stromelysin-1-dependent Invasive Properties

Abstract: Stromelysin-1 is a member of the metalloproteinase family of extracellular matrix-degrading enzymes that regulates tissue remodeling. We previously established a transgenic mouse model in which rat stromelysin-1 targeted to the mammary gland augmented expression of endogenous stromelysin-1, disrupted functional differentiation, and induced mammary tumors. A cell line generated from an adenocarcinoma in one of these animals and a previously described mammary tumor cell line generated in culture readily invaded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
129
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(136 citation statements)
references
References 35 publications
7
129
0
Order By: Relevance
“…Stained cells were mounted in Cytoseal XYL (Stephens Scientific; Kalamazoo, MI, USA) and visualized by epifluorescence as described above. Vimentin expression was detected by indirect immunofluorescence as described previously (Lochter et al, 1997b), with the following exceptions. Confluent cells were grown on MatTek dishes, and the fluorescent-conjugated Alexa 546 goat anti-mouse secondary Ab was used at a final concentration of 2 mg/ml to indirectly detect vimentin expression.…”
Section: Indirect Immunostaining and Image Acquisitionmentioning
confidence: 99%
“…Stained cells were mounted in Cytoseal XYL (Stephens Scientific; Kalamazoo, MI, USA) and visualized by epifluorescence as described above. Vimentin expression was detected by indirect immunofluorescence as described previously (Lochter et al, 1997b), with the following exceptions. Confluent cells were grown on MatTek dishes, and the fluorescent-conjugated Alexa 546 goat anti-mouse secondary Ab was used at a final concentration of 2 mg/ml to indirectly detect vimentin expression.…”
Section: Indirect Immunostaining and Image Acquisitionmentioning
confidence: 99%
“…Overexpression of MMP-3 in mammary gland has previously been shown to increase in vivo branching and cause increased incidence of preneoplastic lesions and invasive breast tumors compared to control mice (Sympson et al, 1995). It was later shown that MMP-3 also induced epithelial-mesenchymal transition (EMT) and malignant transformation in cultured cells (Lochter et al, 1997a;Lochter et al, 1997b;Lochter et al, 1999;Sternlicht et al, 1999). Altogether, it has been clearly demonstrated that deregulation of MMP-3 is a critical occurrence in breast tissue.…”
Section: Discussionmentioning
confidence: 65%
“…Culture medium conditioned by 3D Matrigel cultures for 2 days was processed for casein substrate gels as described previously (Lochter et al, 1997b;Talhouk et al, 1991) In brief, conditioned medium was mixed with zymogram sample buffer without reducing agents, incubated for 15 min at 37 °C, and separated on 8.8% sodium dodecyl sulfate (SDS)-polyacrylamide gels containing 1 mg/ml β-casein (Sigma St. Louis, MO, USA). After electrophoresis, gels were incubated for 30 min with 2.5% Triton X-100 and subsequently for 5 days at 37 °C in 100 mM Tris-HCl, pH 7.4, containing 15 mM CaCl 2 .…”
Section: Zymographymentioning
confidence: 99%
“…Moreover, EWS/ETS expression enhances the ability of UET-13 cells to invade Matrigel. This assay is thought to mimic the early steps of tumor invasion in vivo (34), and the ability to penetrate the Matrigel has been positively correlated with invasion potential in several studies. Therefore, we concluded that EWS/ETS expression could mediate a part of the feature of tumor transformation in human MPCs.…”
Section: Discussionmentioning
confidence: 99%